Bubble or no Bubble - The Impact of Market Model on the Formation of Price Bubbles in Experimental Asset Markets - Michael Kirchler; Jürgen Huber; Thomas Stöckl (University of Innsbruck, Department of Public Finance, 2009)
For the past two decades a market model introduced by Smith, Suchanek, and Williams (1988, henceforth SSW) has dominated experimental research on financial markets. In SSW the fundamental value of the traded asset is determined by the expected value of a finite stream of dividend payments. This setup implies a deterministically falling fundamental value with a predetermined end of the life-span of the asset and extremely high dividend-payouts. We present a new market model in which we implement the fundamental value by adopting a random walk process. Compared to SSW-markets, prices in the new markets (SAVE) are more efficient and end-of-experiment imbalances common in SSW-markets are not observed. Our results demonstrate, that implicit features of the SSW market model contribute to bubble formation.
Keywords: C92; D83; D84; G12; 330; Experimental economics; asset market; bubble; market efficiency; Börsenspiel; Kapitalmarkttheorie; Börsenkurs; Bubbles; Effizienzmarktthese